Implementasi Sistem Penilaian Akreditasi Sekolah/Madrasah di BAN-S/M Provinsi Bali Tahun 2022 Sebagai Wujud Digital Goverment dalam Bidang Pendidikan - I Kadek Nurhayadi; Kadek Rihendra Dantes; I Gusti Ketut Arya Sunu (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to 1) analyze the implementation of the School/Madrasah Accreditation Assessment System at BAN-S/M Bali Province in 2022 as a form of digital government in the education sector in terms of input, process and output variables, 2) find out the benefits and obstacles of implementing an accreditation assessment system Schools/Madrasahs in BAN-S/M Bali Province in 2022 As a Form of Digital Government in the Education Sector. This research is a qualitative descriptive study. The determination of informants in this study used a purposive sampling technique in determining research informants. Data collection techniques using interviews, observation, and documentation from primary data and secondary data. The collected data were analyzed using interactive analysis (interactive model of analysis). The results showed that the implementation of the S/M Sispena in the Bali Province BAN-S/M facilitated school/madrasah accreditation activities carried out by the Bali Province BAN-S/M because the accreditation process went through the S/M Sispena starting from input, process, and output. In terms of input, Sispena S/M has been effective starting from the socialization that was carried out to filling in the School/Madrasah accreditation data entry; from a process standpoint, Sispena S/M is effectively used when mapping adequacy assessments, mapping visits, validation mapping, and assessments by assessors; and from an output perspective, Sispena S/M is very practical. Schools/madrasas can download the accreditation certificate directly from the Sispena S/M account. M and see the recommendations for accreditation results which are used as a reference for improving the quality of education in schools/madrasas. The main obstacle in implementing the S/M Sispena is the unavailability of an internet network at schools/madrasahs which hinders filling in accreditation entry data at Sispena because the S/M Sispena is a web-based system that must be connected to the internet network to operate it.